Analysis of the transient thermal field in two conductors carrying sinusoidal current using Green's function - Zaręba, Marek (Archives of Electrical Engineering (Online), 2025)
This paper analyzes the transient thermal field in a system of two parallel con-ductors. The skin and proximity effects are taken into account. An analytical method based on Green’s function is developed to determine the field distributions. The Green's function was determined analytically, and due to the complex forms of the expressions describing the current densities, the integrals resulting from the Green's identity were calculated nu-merically. In addition, important parameters determining the dynamics of the conductors were also calculated: heating curves and thermal time constants. The influence of selected material parameters on the corresponding thermal field distributions is examined. The cal-culation results are positively verified using the finite element method.